2012
DOI: 10.1002/ajhb.22281
|View full text |Cite
|
Sign up to set email alerts
|

Physical strength, fighting ability, and aggressiveness in adolescents

Abstract: With reference to the recalibrational theory of anger, our results suggest that the sex- and age-dependent associations between fighting ability and physical and nonphysical aggression indicate divergent adaptive skills between sexes, which are driven by intrasexual competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 58 publications
2
46
0
6
Order By: Relevance
“…Second, due to data constraints, we were forced to rely only on the measures of height and bulk to assess physical stature as proxies for fighting skills. While this measurement strategy may be an advantage over previously used measures of fighting ability, such as hand grip strength [34], a more comprehensive measure would have been more ideal. Follow-up research should build upon these findings to determine the extent to which other skills, such as hand-eye coordination and objective measures of muscle strength, are able to predict being a skilled physical fighter among adolescent males.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to data constraints, we were forced to rely only on the measures of height and bulk to assess physical stature as proxies for fighting skills. While this measurement strategy may be an advantage over previously used measures of fighting ability, such as hand grip strength [34], a more comprehensive measure would have been more ideal. Follow-up research should build upon these findings to determine the extent to which other skills, such as hand-eye coordination and objective measures of muscle strength, are able to predict being a skilled physical fighter among adolescent males.…”
Section: Discussionmentioning
confidence: 99%
“…As in other animal species (Arnott & Elwood, 2009), fighting ability in men is specifically linked to strength (Archer & Thanzami, 2007;Muñoz-Reyes, Gil-Burmann, Fink, & Turiegano, 2012;Sell, Cosmides, et al, 2009), although several relationships have been proposed for other traits (e.g., facial masculinity in Sell, Cosmides, et al, 2009). Accordingly, some studies have demonstrated the relationship between hand grip strength (HGS henceforth) and fighting ability for male-male competition (e.g., Muñoz-Reyes et al, 2012;Sell, Cosmides, et al, 2009 (Sell, Tooby, et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Accordingly, some studies have demonstrated the relationship between hand grip strength (HGS henceforth) and fighting ability for male-male competition (e.g., Muñoz-Reyes et al, 2012;Sell, Cosmides, et al, 2009 (Sell, Tooby, et al, 2009). In addition, positive associations between male HGS as a proxy of fighting ability and the number of sexual partners have been observed (Gallup, White, & Gallup, 2007; for a composite index that includes HGS, see Lukaszewski, Larson, Gildersleeve, Roney, & Haselton, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…This may facilitate them to develop higher muscularity, given the significance of testosterone on the expression of muscle size and physical strength (Bhasin et al, 1996;Finkelstein et al, 2013), which may also have positive consequences on the expression of testosterone related masculine male traits, which reflect high RHP. Thus our findings may explain why physical strength is not only a feature that is important in intra-sexual selection (Muñoz-Reyes et al 2012;Sell et al, 2009Sell et al, , 2012 but also in inter-sexual selection. However, it also suggests that in males muscular strength may be a measure of male quality independent of its role in mediating malemale interactions.…”
Section: Discussionmentioning
confidence: 85%